Interhemispheric claustral circuits coordinate sensory and motor cortical areas that regulate exploratory behaviors - Smith, Jared B.; Alloway, Kevin D. (Frontiers in Systems Neuroscience, 2014)
The claustrum has a role in the interhemispheric transfer of certain types of sensorimotor information. Whereas the whisker region in rat motor (M1) cortex sends dense projections to the contralateral claustrum, the M1 forelimb representation does not. The claustrum sends strong ipsilateral projections to the whisker regions in M1 and somatosensory (S1) cortex, but its projections to the forelimb cortical areas are weak. These distinctions suggest that one function of the M1 projections to the contralateral claustrum is to coordinate the cortical areas that regulate peripheral sensor movements during behaviors that depend on bilateral sensory acquisition. If this hypothesis is true, then similar interhemispheric circuits should interconnect the frontal eye fields (FEF) with the contralateral claustrum and its network of projections to vision-related cortical areas. To test this hypothesis, anterograde and retrograde tracers were placed in physiologically-defined parts of the FEF and primary visual cortex (V1) in rats. We observed dense FEF projections to the contralateral claustrum that terminated in the midst of claustral neurons that project to both FEF and V1. While the FEF inputs to the claustrum come predominantly from the contralateral hemisphere, the claustral projections to FEF and V1 are primarily ipsilateral. Detailed comparison of the present results with our previous studies on somatomotor claustral circuitry revealed a well-defined functional topography in which the ventral claustrum is connected with visuomotor cortical areas and the dorsal regions are connected with somatomotor areas. These results suggest that subregions within the claustrum play a critical role in coordinating the cortical areas that regulate the acquisition of modality-specific sensory information during exploration and other behaviors that require sensory attention.